Antioxidant and Immunostimulatory Activities of Fermented Sour Soybean Milk Added With Polypeptides From Pleurotus eryngii - Song, Xinling; Xu, Ximin; Chen, Wei (Frontiers in Microbiology, 2022)
The improved quality of sour soybean milk by adding polypeptide from Pleurotus eryngii was investigated in this study, and the immunomodulatory effect of sour soybean milk fermented with polypeptides from P. eryngii was also evaluated in immunosuppressed mice induced by cyclophosphamide. Results showed the physicochemical property of sour soybean milk fermented with small-molecular-weight polypeptide (<3 kDa) were superior to the others including the decrease of pH, and increase of acidity, water-holding capacity and lactic acid bacteria count. The animal experiment demonstrated that sour soybean milk with polypeptide could effectively reverse the decreasing trend of thymus/spleen index and hematological parameters, enhance murine immune functions including serum hemolysin and splenic lymphocyte proliferation, and inhibit oxidative stress. In addition, sour soybean milk fermented with polypeptide could increase the diversity of intestinal flora, and increase the abundances of Firmicutes, Bacteroides, and Lactobacillus. Taken together, it could provide a theoretical basis for developing an immunomodulatory agent or functional food additives with antioxidant activity.